Transactions on Aspect-Oriented Software Development IX - Leavens, Gary T.; Chiba, Shigeru; Haupt, Michael; Ostermann, Klaus; Wohlstadter, Eric.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The LNCS journal Transactions on Aspect-Oriented Software Development is devoted to all facets of aspect-oriented software development (AOSD) techniques in the context of all phases of the software life cycle, from requirements and design to implementation, maintenance and evolution. The focus of the journal is on approaches for systematic identification, modularization, representation and composition of crosscutting concerns, i.e., the aspects and evaluation of such approaches and their impact on improving quality attributes of software systems. This volume, the 9th in the Transactions on Aspect-Oriented Software Development series, contains three regular submissions and two special sections, each consisting of two papers. The papers focus on the following topics: modularization, pointcut language, dynamic adaptation, event-based programming, aspect-aware design, system software, object composition and templates.
Domain-Driven Discovery of Stable Abstractions for Pointcut Interfaces -- Aspect of Assembly: From Theory to Performance -- Dynamic Aspect-Oriented Programming in Java: The HotWave Experience -- Abstracting Context in Event-Based Software -- The Aspect-Aware Design and Implementation of the CiAO Operating-System Family -- First-Class Compositions: Defining and Composing Object and Aspect Compositions with First-Class Operators -- Challenges in the Design of the Package Template Mechanism.
Keywords: Computer science; Software engineering; Logic design; Computer simulation; Information Systems; Computer Science; Software Engineering; Programming Languages, Compilers, Interpreters; Logics and Meanings of Programs; Programming Techniques; Simulation and Modeling; Management of Computing and Information Systems